CONGENITAL LENS COLOBOMA AND ASSOCIATED PATHOLOGIES - (:unkn) unknown (KLUWER ACADEMIC PUBL, 1993)
Coloboma of the lens is characterized by notching of the equator of the lens. The cause of the condition is faulty development of the zonule. The lens deprived of its normal pull in the defective region is thicker and more spherical as if there were no loss of its substance. We report five cases of lens coloboma and localized zonular defect without any associated systemic anomalies. One case included retinal detachment; another included an iris coloboma; and a third included iris, choroid and optic disk colobomas and retinal detachment with lens coloboma. The remaining two cases were without associated ocular anomalies. The pathogenic mechanisms and relationship of this defect with the differentiation of the tertiary vitreous and development of the zonule is discussed. The defect most likely occurs in the third to fourth months of gestation during differentiation of the tertiary vitreous in response to toxic, inflammatory or genetic factors.
Keywords: CONGENITAL LENS COLOBOMA; COLOBOMA OF THE IRIS; COLOBOMA OF THE CHOROID; COLOBOMA OF THE OPTIC DISK; RETINAL DETACHMENT